2016
DOI: 10.1111/bcp.13052
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation induced by inhaled lipopolysaccharide depends on particle size in healthy volunteers

Abstract: AIMSIn drug development, the anti-inflammatory properties of new molecules in the lung are currently tested using the inhaled lipopolysaccharide (LPS) model. The total and regional lung bioavailability of inhaled particles depends significantly on their size. The objective of the present study was to compare inflammatory responses in healthy volunteers after the inhalation of LPS of varying droplet size. METHODSThree nebulizers were characterized by different droplet size distributions [mean mass median aerody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…55 In humans, inhalation of lipopolysaccharides induces neutrophilic inflammation. 56 Hence, lipopolysaccharides could be correlated with neutrophilic inflaming. Moreover, the Spearman correlation heat map showed that these bacterial species were significantly positively correlated with TWBCs and neutrophil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 In humans, inhalation of lipopolysaccharides induces neutrophilic inflammation. 56 Hence, lipopolysaccharides could be correlated with neutrophilic inflaming. Moreover, the Spearman correlation heat map showed that these bacterial species were significantly positively correlated with TWBCs and neutrophil.…”
Section: Discussionmentioning
confidence: 99%
“…lipopolysaccharides help to induce neutrophilic asthma in a mouse model 55 . In humans, inhalation of lipopolysaccharides induces neutrophilic inflammation 56 . Hence, lipopolysaccharides could be correlated with neutrophilic inflaming.…”
Section: Discussionmentioning
confidence: 99%
“…The CC16 protein protects the respiratory tract against oxidative stress and is a potent anti-inflammatory agent (Janicova et al, 2019;Pang et al, 2017). The inflammatory reaction occurring in the lungs, leads to an increased production of CC16, resulting in increased levels of serum CC16 (Arsalane et al, 2000;Barregard et al, 2008;Doyen et al, 2016;Seys et al, 2015). The time needed for this increase to occur and to be observed, can vary depending on the source and the levels of the toxicant causing the inflammation.…”
Section: Fig 1 Multivariable Analysis Of the Association Between Urin...mentioning
confidence: 99%
“…The time needed for this increase to occur and to be observed, can vary depending on the source and the levels of the toxicant causing the inflammation. Irritants such as ozone (Alexis et al, 2008;Arsalane et al, 1999;Blomberg et al, 2003;Broeckaert et al, 2000), smoke (Rosenberg and Kalhan, 2012;Stockfelt et al, 2012) and lipopolysaccharides (Doyen et al, 2016;Michel et al, 2005) lead to serum CC16 levels rapidly increasing within a few hours after exposure. Similarly, serum CC16 increased in the first 2 h and lasted up to 24 h after PM 2.5 exposure (Wang et al, 2017a).…”
Section: Fig 1 Multivariable Analysis Of the Association Between Urin...mentioning
confidence: 99%
“…Relatie tussen de waargenomen longdepositie van endotoxine en het optreden van een systemische ontstekingsreactie, bepaald als CRP (C-reactief proteïne) concentratie in bloed, 24 uur na inhalatie van endotoxine. Figuur overgenomen (met toestemming) uit Doyen et al (2016).…”
Section: Figuur 10unclassified